Risk Factors Affecting Dry Eye Symptoms among Visual Display Terminal Users - Chaihan Rungsirisangratana; Nawiya Nuntapanich; Patima Pinsuwannabud; Sukanya Teangkumdee (The Indonesian Journal of Occupational Safety and Health, 2022)
Introduction: Dry eye symptoms are the common ocular complaints that are found at the ophthalmologic outpatient services. This research’s main purposes were to study the risk factors associated with dry eye symptoms and to evaluate the severity of dry eye among Visual Display Terminal (VDT) users. Methods: This study was a descriptive observational study involving 104 VDT users in 3 branches of the Social Security Offices and the Bureau of Labor Protection and Welfare in Samutprakarn province, Thailand. The study instruments used were: (1) questionnaires associated with VDT use and dry eye symptoms that were evaluated by using the Ocular Surface Disease Index (OSDI) and (2) Lux meter for desk-brightness and the angle of gaze measurement during VDT use. Data were analyzed using a Chi-square test and multiple logistic regression. Results: The results found that VDT users had severe dry eye symptoms, accounting for 51.9%, and experienced moderate and mild dry eye symptoms in the same number, which was 24.0%. In addition, dry eye symptoms were related to VDT use for 5-7 hours/day with statistically significant value. Other VDT use factors, including the desk-brightness or the angle of gaze during VDT use, were related to severe dry eye symptoms with no statistically significant difference. Conclusion: Based on the findings, VDT users should use VDT no more than 5 hours/day in order to reduce VDT-related dry eye symptoms. these factors were not statistically significant for the occurrence of severe dry eye symptoms.